Multisite Thrombus Imaging and Fibrin Content Estimation With a Single Whole-Body PET Scan in Rats. Issue 10 (October 2015) - Blasi, Francesco; Oliveira, Bruno L.; Rietz, Tyson A.; Rotile, Nicholas J.; Naha, Pratap C.; Cormode, David P.; Izquierdo-Garcia, David; Catana, Ciprian; Caravan, Peter
Abstract : Objective—: Thrombosis is a leading cause of morbidity and mortality worldwide. Current diagnostic strategies rely on imaging modalities that are specific for distinct vascular territories, but a thrombus-specific whole-body imaging approach is still missing. Moreover, imaging techniques to assess thrombus composition are underdeveloped, although therapeutic strategies may benefit from such technology. Therefore, our goal was to test whether positron emission tomography (PET) with the fibrin-binding probe 64 Cu-FBP8 allows multisite thrombus detection and fibrin content estimation. Approach and Results—: Thrombosis was induced in Sprague-Dawley rats (n=32) by ferric chloride application on both carotid artery and femoral vein. 64 Cu-FBP8-PET/CT imaging was performed 1, 3, or 7 days after thrombosis to detect thrombus location and to evaluate age-dependent changes in target uptake. Ex vivo biodistribution, autoradiography, and histopathology were performed to validate imaging results. Arterial and venous thrombi were localized on fused PET/CT images with high accuracy (97.6%; 95% confidence interval, 92–100). A single whole-body PET/MR imaging session was sufficient to reveal the location of both arterial and venous thrombi after 64 Cu-FBP8 administration. PET imaging showed that probe uptake was greater in younger clots than in older ones for both arterial and venous thrombosis ( P <0.0001). Quantitative histopathology revealed an age-dependent reduction of thrombus fibrin content ( P <0.001), consistent with PET results. Biodistribution and autoradiography further confirmed the imaging findings. Conclusions—: We demonstrated that 64 Cu-FBP8-PET is a feasible approach for whole-body thrombus detection and that molecular imaging of fibrin can provide, noninvasively, insight into clot composition. Abstract : Supplemental Digital Content is available in the text.